Realistic Mathematics Education Based on Virtual Network in Increasing the Understanding of Geometry Concept - Octarina Hidayatus Sholikhah; Rasmita Rasmita (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This article was to improve the understanding of elementary school students' geometry concepts through the Realistic Mathematic Education (RME) model that assisted by virtual nets. This research was classroom action research. This research was conducted in two cycles where each cycle had two meetings. The research subjects were the fifth grade students. In this study two cycles were carried out where if the first cycle had not yet reached the specified indicators. It would be improved in the next cycle or the second cycle. Data collection techniques used tests and observations in each cycle. In the second cycle it was felt that the target had been reached, so that the study would end until the second cycle. At the pre-cycle stage obtained a classical percentage of 50%, the first cycle obtained a percentage of 70% and in the second cycle increased by 100%. Thus the researcher concludes that through the RME model assisted by virtual nets can improve the understanding of geometrical concepts of elementary school students. Keywords: Virtual Network, RME, Realistic Mathematics Education